Fruit sanitize postharvest / Awangku Syazwie Awangku Hyrul, Syazarul Azrie Johansah and Nizam Abdullah - Awangku Hyrul, Awangku Syazwie; Johansah, Syazarul Azrie; Abdullah, Nizam (Faculty of Plantation and Agrotechnology, 2023)
Postharvest management begins with disinfecting fresh fruits and vegetables. Disinfection techniques eliminate fungal postharvest pathogens and bacterial human pathogens to improve food safety. Disinfection directly reducing postharvest microorganisms that build on fruit surfaces before and during harvest helps avoid storage rot. This overview covers the history, chemistry, and regulations of some key disinfectants. Chlorine, chlorine dioxide, ozone, ethanol, hydrogen peroxide, organic acids, and electrolyzed water. Some of the disinfectants in this review have been used for years, while others are 'alternative' and new. Experimental reports, practical application, phytotoxicity, residues, advantages, disadvantages, and mode of action of chemicals and technologies are discussed. Due to their untapped potential, vapor and gas phase applications and several associated technologies are highlighted. Disinfection is a key strategy for managing postharvest degradation of fresh fruit, according to this review. In some circumstances, disinfection is a precondition for important postharvest technologies, and it can become the dominant technology. This review found that chemical disinfectants' poor reputation is unwarranted because they leave no or non-toxic residues and their environmental impact is modest compared to their benefits.